Economic Valuation of Natural Resources in Gunung Rinjani: Implications for Sustainable Development - M. Zulkifli Amin (Journal of Economic Perspectives and Business Innovation, 2025)
AbstractThe economic valuation of natural resources is essential for designing policies that balance environmental conservation with regional development. This study evaluates the economic value of natural resources in the Gunung Rinjani area and examines its implications for sustainable development. Using a quantitative and descriptive approach, the research applies environmental valuation methods to estimate the direct and indirect benefits derived from tourism, biodiversity, and ecosystem services. The findings show that Gunung Rinjani provides significant economic contributions to local communities while also serving as a critical ecological asset. However, unsustainable exploitation and inadequate management threaten long-term benefits. The study concludes that integrating economic valuation into planning and policy decisions can support conservation efforts, improve resource governance, and promote sustainable development strategies that protect both economic and environmental interests. Keywords: economic valuation, natural resources, sustainable development, ecosystem services, Gunung Rinjani